"Unreasonable" ventricular pacings. Issue 2 (21st August 2020) - Zhang, Yubin; Liu, Tong; Korantzopoulos, Panagiotis
Abstract : A 66‐year‐old man, implanted Abbott dual‐chamber pacemaker, was admitted to our hospital due to recurrent palpitation. ECG was recorded on admission, which created a diagnostic confusion: What accounts for the appearance of the VP in the setting of a stable intrinsic atrioventricular (AV) conduction? In this case, we will focus on the logical reasoning in the analysis of Pacing ECG.